Stabilization and Reform in Eastern Europe : A Preliminary Evaluation - Bruno, Michael (IMF Working Papers; Working Paper, 1992)
The paper analyzes common issues emerging from the recent experience with Fund-supported programs in Hungary, Poland, Czechoslovakia, Bulgaria and Romania. These comprise the initial price-overshooting and the output collapse, fiscal sustainability as well as the financial and structural problems associated with bad loan portfolios and sluggish implementation of privatization programs. Substantial success, in varying degrees, has been achieved in the initial macro-stabilization and opening-up effort. At the same time mounting difficulties with fiscal and monetary control may be emerging, as a result of social and political pressures and insufficiently clear policy signals on the micro-issues involving the sharp structural transformation of the productive and financial systems.